2013
DOI: 10.1128/jb.00431-13
|View full text |Cite
|
Sign up to set email alerts
|

Role for Skp in LptD Assembly in Escherichia coli

Abstract: The periplasmic chaperone Skp has long been implicated in the assembly of outer membrane proteins (OMPs) in Escherichia coli. It has been shown to interact with unfolded OMPs, and the simultaneous loss of Skp and the main periplasmic chaperone in E. coli, SurA, results in synthetic lethality. However, a ⌬skp mutant displays only minor OMP assembly defects, and no OMPs have been shown to require Skp for their assembly. Here, we report a role for Skp in the assembly of the essential OMP LptD. This role may be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 54 publications
3
45
0
2
Order By: Relevance
“…Our conclusion of the different degrees of importance of SurA, Skp, and FkpA for the biogenesis of OMPs at the normal temperature (i.e., SurA Ͼ Skp Ͼ FkpA) also finds support from a recent study by Schwalm et al, who observed that the single deletion of surA rather than skp or fkpA significantly decreased the level of folded LptD and that the double deletion of bamB and skp led to a more severe defect in LptD folding than the double deletion of bamB and fkpA (45). Notably, they also reported that the double deletion of skp and fkpA led to a significant reduction in the levels of LptD and FhuA and that the overexpression of FkpA was unable to restore the LptD assembly defect of a ⌬surA mutant under normal growth temperatures (45).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our conclusion of the different degrees of importance of SurA, Skp, and FkpA for the biogenesis of OMPs at the normal temperature (i.e., SurA Ͼ Skp Ͼ FkpA) also finds support from a recent study by Schwalm et al, who observed that the single deletion of surA rather than skp or fkpA significantly decreased the level of folded LptD and that the double deletion of bamB and skp led to a more severe defect in LptD folding than the double deletion of bamB and fkpA (45). Notably, they also reported that the double deletion of skp and fkpA led to a significant reduction in the levels of LptD and FhuA and that the overexpression of FkpA was unable to restore the LptD assembly defect of a ⌬surA mutant under normal growth temperatures (45).…”
Section: Discussionsupporting
confidence: 63%
“…Notably, they also reported that the double deletion of skp and fkpA led to a significant reduction in the levels of LptD and FhuA and that the overexpression of FkpA was unable to restore the LptD assembly defect of a ⌬surA mutant under normal growth temperatures (45). We noticed that LptD and FhuA are large (87 kDa and 79 kDa, respectively), both containing a transmembrane ␤-barrel domain and a soluble periplasmic domain.…”
Section: Discussionmentioning
confidence: 86%
“…It had been previously demonstrated that many of the OMP assembly factors, including chaperones and BAM complex members, function in overlapping and redundant pathways (4,14,27). Indeed, a role for the SurA P1 domain in vivo was revealed only when surA10 was isolated in a background defective for BAM complex function (27).…”
Section: Deletion Of the Second Parvulin Domain Results In Inhibition Ofmentioning
confidence: 99%
“…SurA is also thought to be the terminal chaperone in the assembly process, as it is the only chaperone known to interact with the periplasmic polypeptide-transport-associated (POTRA) domains of the BAM insertase BamA and, as the deletion of surA affects OMP maturation in the same manner as the loss of BamB, one of the four BamAassociated lipoprotein members of the BAM complex (4,11,12). Despite its central role in OMP assembly, SurA is not essential, because a redundant network of other chaperones, notably Skp, FkpA, and the chaperone/protease DegP, is sufficient to maintain viability in the absence of SurA (13,14).The functions of several periplasmic chaperones were better elucidated when it was discovered that their three-dimensional structures resemble those of well-known cytoplasmic chaperones and folding factors. The trimeric jellyfish structure of the functional Skp chaperone, for example, resembles that of cytosolic prefoldin, and Skp sequesters substrates in a manner mechanisti- …”
mentioning
confidence: 99%
“…It functions as a chaperone in vivo, promoting assembly of OMPs. FkpA function overlaps Skp function at least in part, and both seem to be involved in assembly of the essential OMP LptD (37), which is in turn responsible for inserting lipopolysaccharide (LPS) into the OM of Gram-negative bacteria like E. coli (38,39). In the present study, we found that disruption of fkpA leads to a 2-to 3-fold reduction in whole-cell ␤-galactosidase activity in cells expressing the malF-lacZ102 fusion in the absence of DsbA.…”
Section: Discussionmentioning
confidence: 99%